Recession Response: Cyclical Problems and Local Solutions in Northern British Columbia. (14th July 2015) - Manson, Don; Markey, Sean; Ryser, Laura; Halseth, Greg
Abstract: The purpose of this paper is to trace community and regional responses to the economic downturn of 2008/2009 in Northern British Columbia, Canada. Our research during this period (2009–2011), the Northern Economic Vision II (NEV II) project, sought to investigate whether communities in the region were incorporating some of the core findings, lessons from an earlier project, the NEV I project (conducted in 2002–2005), in terms of preparing for both economic uncertainty and opportunity through place‐oriented community planning and enhanced regional collaboration. Findings suggest that in the face of economic hardship, many communities continued to pursue community and regionally‐oriented strategies in an attempt to preserve services and quality of life for local residents, and did not engage in reactive budget cuts in the face of economic decline, as experienced in previous bust periods.